Thick anti-cracking middle layer coating and preparation method thereof
By using thick anti-cracking medium coatings of coconut fiber and other components, the existing medium coatings are easily cracked and high energy consumption and high pollution of cement during single-channel construction, and the single-channel construction thickness exceeds 20mm and environmental protection is achieved. Performance improvement.
Patent Information
- Application Number
- CN202211338598.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-10-28
AI Technical Summary
The existing middle-layer coating is prone to cracking when the single-channel construction exceeds 2mm, and the use of cement as adhesives has high energy consumption and high pollution problems. It is urgent to develop a middle-layer coating that does not crack in a single-channel construction exceeds 20mm and has thermal insulation function. .
Thick anti-cracking medium coating with coconut fiber, cement, silicon fume, oxidized polyethylene, light aggregate, desulfurization gypsum, retarder and cellulose, and the addition of coconut fibers will replace part of the cement to improve the material's resistance. Compressive strength and toughness, and improve the tiling properties of coconut fibers by oxidizing polyethylene.
The single-channel construction thickness reaches 20mm-40mm without cracking, saving labor costs, and by replacing cement with coconut fiber, the compressive strength and environmental protection performance of the material are improved, while maintaining good corrosion resistance and aging resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of construction engineering, and in particular to a thick anti-cracking middle layer coating and a preparation method thereof. Background Art
[0002] The building middle-layer coating industry has had a profound impact on people's lives. The middle-layer coatings used in building materials are now mainly putty. Putty is prone to cracking if a single coat exceeds 2mm during use. For uneven walls, multiple coats can only be applied, which wastes time and labor.
[0003] In addition, in the existing technology, the main adhesive for the middle layer coating is cement, which is a high-energy consumption and high-pollution raw material. In order to be green, low-carbon and environmentally friendly, the amount of cement should be reduced and replaced by environmentally friendly green renewable resources.
[0004] Therefore, it is urgent to develop a middle layer coating that does not crack when a single-pass construction exceeds 20 mm and has thermal insulation functions. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a thick anti-cracking middle layer coating and a preparation method thereof, so as to solve the problems in the prior art.
[0006] In order to achieve the above-mentioned and other related purposes, one aspect of the present invention provides a thick anti-cracking middle layer coating, wherein the raw materials of the coating include the following components by weight percentage:
[0007]
[0008] In some embodiments of the present invention, the raw materials of the coating include the following components by weight percentage:
[0009]
[0010]
[0011] In some embodiments of the present invention, the length of the coconut fiber is 4 to 9 mm.
[0012] In some embodiments of the present invention, the diameter of the coconut fiber is 10 to 20 microns.
[0013] In some embodiments of the present invention, the cement is selected from Portland cement; the cement is preferably No. 42.5 Portland cement.
[0014] In some embodiments of the present invention, the molecular weight of the oxidized polyethylene is 1000-1500.
[0015] In some embodiments of the present invention, the light aggregate is selected from a combination of one or more of glass microspheres and polystyrene particles; preferably, the mesh size of the light aggregate is 70 to 100 meshes.
[0016] In some embodiments of the present invention, the retarder is selected from a combination of one or more of protein retarders, hydroxyhydroxy acid salts, and phosphates.
[0017] In some embodiments of the present invention, the cellulose is selected from a combination of one or more of hydroxypropyl methylcellulose, methyl cellulose, and hydroxyethyl cellulose; and the molecular weight of the cellulose is 30,000 to 100,000.
[0018] Another aspect of the present invention provides a method for preparing the thick anti-cracking middle layer coating as described above, comprising mixing coconut fiber, cement, silica fume, oxidized polyethylene, light aggregate, desulfurized gypsum, retarder and cellulose.
[0019] Another aspect of the present invention provides use of the thick anti-cracking middle layer coating according to the present invention in the field of construction.
[0020] The thick anti-cracking middle layer coating provided by the present invention has the following beneficial effects:
[0021] 1. Ordinary middle layer or putty is very easy to crack when applied in a single coat over 2mm. For walls with uneven base surfaces, multiple constructions are required. However, after adding coconut fiber, a single coat of 20mm-40mm will not crack. Only a single coat is needed to complete the middle layer construction on walls with uneven base surfaces, saving a lot of labor.
[0022] 2. When coconut fiber is added to replace cement, the overall compressive strength of the material increases rapidly and linearly by 0%-35%. When the compressive strength of the middle layer material reaches 2%, the rising rate area reaches the inflection point and becomes stable. Therefore, its characteristics can be used to replace part of the cement in the middle layer material, thus generating energy-saving and emission reduction benefits.
[0023] 3. Coconut fiber is extracted from waste coconut shells and has a high cost-effectiveness. As a natural renewable material, it has excellent aging resistance in high salinity and alkali environments. While improving the performance of the middle layer material, it also maintains good corrosion resistance and aging resistance. Its excellent toughness can increase the flexibility and ductility of the coating and has excellent crack resistance.
[0024] 4. The present invention makes it easier to spread the coconut fiber with high toughness in the middle layer coating by adding oxidized polyethylene. DETAILED DESCRIPTION
[0025] The following is a detailed description of an embodiment of a thick anti-cracking middle layer coating and a preparation method thereof of the present application.
[0026] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0027] The inventor of the present invention has adopted green renewable resource coconut fiber through a large number of exploration experiments. Its characteristics are high toughness and salt water resistance (not easy to be corroded in cement). When replacing part of cement, it can improve the overall strength and toughness of the material and has good aging resistance. However, due to its characteristics, it is not easy to lay flat in the material. Therefore, the present invention overcomes this problem through the synergy between multiple components and coconut fiber, and obtains a thick anti-cracking middle layer coating. On this basis, the present invention is completed.
[0028] One aspect of the present invention provides a thick anti-cracking middle layer coating, the raw materials of which include coconut fiber, cement, silica fume, oxidized polyethylene, light aggregate, desulfurized gypsum, retarder, cellulose and the like.
[0029] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials include 1% to 4% coconut fiber according to the weight percentage of the thick anti-cracking middle layer coating. In some embodiments, the weight percentage of the coconut fiber can also be 1% to 2%, 2% to 4%, 2% to 3%, or 3% to 4%. The coconut fiber in the present invention has high flexibility and high salt water resistance. When the present invention is used, under normal circumstances, the coconut fiber needs to meet a certain length, and the length of the coconut fiber can be, for example, 4 to 9mm, 4 to 6mm, 6 to 9mm, 4 to 5mm, 5 to 6mm, 6 to 7mm, 7 to 8mm, or 8 to 9mm. The diameter of the coconut fiber can be 10 to 20 microns, 10 to 15 microns, 15 to 20 microns, 10 to 13 microns, 13 to 15 microns, 15 to 18 microns, or 18 to 20 microns.
[0030] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials include 30% to 50% cement according to the weight percentage of the thick anti-cracking middle layer coating. In some embodiments, the weight percentage of cement can also be 30% to 35%, 35% to 45%, 30% to 40%, 40% to 50%, 30% to 45%, or 45% to 50%. In some embodiments, the cement is selected from silicate cement. Specifically, silicate cement can be, for example, 42.5 silicate cement. The role of using cement is as an adhesive.
[0031] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials include 5% to 15% of silica ash according to the weight percentage of the thick anti-cracking middle layer coating. In some embodiments, the weight percentage of silica ash can also be 5% to 8%, 8% to 12%, 12% to 15%, 5% to 10%, 10% to 15%, 5% to 8%, 8% to 10%, or 10% to 12%, etc. Silica ash, also called silica powder and microsilica powder, has the appearance of gray or grayish white powder and a refractoriness of >1600°C. Bulk density: 200 to 250 kg / cubic meter. More than 80% of the silica ash has a fineness of less than 1 μm, the average particle size is 0.1 to 0.3 μm, and the specific surface area is: 20 to 28 m 2 / g. Its fineness and specific surface area are about 80 to 100 times that of cement and 50 to 70 times that of fly ash. In the present invention, the mesh size of silica fume can be, for example, 100 mesh to 400 mesh, 100 mesh to 200 mesh, 200 mesh to 300 mesh, or 300 mesh to 400 mesh. Silica fume can fill the pores between cement particles.
[0032] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials include 0.5% to 1% of oxidized polyethylene according to the weight percentage of the thick anti-cracking middle layer coating. In some embodiments, the weight percentage of oxidized polyethylene can also be 0.5% to 0.8%, 0.8% to 1%, 0.5% to 0.6%, 0.6% to 0.7%, 0.7% to 0.8%, 0.8% to 0.9%, or 0.9% to 1%, etc. In the present invention, the molecular weight of oxidized polyethylene can be, for example, a mixture formed by the condensation of ethylene oxide and water. The molecular formula is OH(CH2CH2O) nH represents, wherein n represents the average number of oxyethylene groups, and the value of n can be 22-30, 22-24, 24-26, 26-28, or 28-30, etc. The molecular weight of the oxidized polyethylene is greater than 1000. In some embodiments, the molecular weight of the oxidized polyethylene can be 1000-1500, 1000-1200, 1200-1500, 1000-1100, 1100-1200, 1200-1300, 1300-1400, or 1400-1500, etc. Oxidized polyethylene is a white granular substance, soluble in water and in some organic solvents. Its solution has high viscosity at low concentrations and can be processed by calendering, extrusion, casting, etc. It is a thermoplastic resin with good compatibility with other resins. It is resistant to bacterial erosion and has weak hygroscopicity in the atmosphere. Coconut fiber has high toughness and is not easy to be spread in the middle layer coating. The applicant has found that this problem can be solved by adding oxidized polyethylene (polyethylene glycol) to the material. Oxidized polyethylene (polyethylene glycol) belongs to a non-ionic linear macromolecular polymer, which can be wrapped on the surface of coconut fiber to make it moisturizing, lubricating and soft, thereby making it soft and easy to spread in stirring without destroying the coconut fiber.
[0033] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials are calculated according to the weight percentage of the thick anti-cracking middle layer coating, including 15% to 25% of light aggregate. In some embodiments, the weight percentage of light aggregate can also be 15% to 25%, 15% to 20%, 20% to 25%, 15% to 18%, 18% to 20%, 20% to 22%, or 22% to 25%, etc. In some embodiments, the light aggregate is selected from a combination of one or more of vitrified microspheres, white vermiculite, polystyrene particles, etc. Specifically, the light aggregate can be, for example, 70 to 100 mesh, 70 to 80 mesh, 80 to 90 mesh, or 90 to 100 mesh. Further, the light aggregate is preferably selected from vitrified microspheres. The vitrified microspheres can be, for example, 70 to 100 mesh, 70 to 80 mesh, 80 to 90 mesh, or 90 to 100 mesh.
[0034] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials include 5% to 25% desulfurized gypsum according to the weight percentage of the thick anti-cracking middle layer coating. In some embodiments, the weight percentage of the desulfurized gypsum can also be 5% to 10%, 10% to 15%, 15% to 20%, 20% to 25%, 5% to 20%, 5% to 15%, or 15% to 25%. The role of desulfurized gypsum is to assist in improving the initial strength of the product.
[0035] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials include 0.05% to 0.1% of retarder according to the weight percentage of the thick anti-cracking middle layer coating. In some embodiments, the weight percentage of the retarder can also be 0.05% to 0.08%, or 0.08% to 0.1%, etc. The retarder in the present invention can be, for example, a combination of one or more of protein retarders, hydroxyhydroxy acid salts, phosphates, etc. The function of the retarder is to adjust the initial and final setting time of the desulfurized gypsum.
[0036] In the thick anti-cracking middle layer coating provided by the present invention, the raw materials, calculated according to the weight percentage of the thick anti-cracking middle layer coating, also include 0.3% to 0.5% cellulose. In some embodiments, the weight percentage of the cellulose can be, for example, 0.3% to 0.4%, 0.4% to 0.5%, 0.3% to 0.35%, 0.35% to 0.4%, 0.4% to 0.45%, or 0.45% to 0.5%, etc. The cellulose is selected from a combination of one or more of hydroxypropyl methylcellulose, methyl cellulose, hydroxyethyl cellulose, etc. The molecular weight of the cellulose can be 30,000 to 100,000, 30,000 to 50,000, 50,000 to 80,000, or 80,000 to 100,000, etc. The role of cellulose is to improve the water retention of the product.
[0037] In a specific embodiment of the present invention, the raw materials of the thick anti-cracking middle layer coating include the following components by weight percentage:
[0038]
[0039] In a preferred embodiment of the present invention, the raw materials of the thick anti-cracking middle layer coating include the following components by weight percentage:
[0040]
[0041] Another aspect of the present invention provides a method for preparing the thick anti-cracking middle layer coating, the method comprising: mixing coconut fiber, cement, silica fume, oxidized polyethylene, light aggregate, desulfurized gypsum, retarder and cellulose.
[0042] In the preparation method of the thick anti-cracking middle layer coating provided by the present invention, specifically, coconut fiber, cement, silica fume, oxidized polyethylene, light aggregate, desulfurized gypsum, retarder, and cellulose are mixed according to the proportion provided by the first aspect of the present invention. For example, they can be mixed at a certain stirring speed. Specifically, for example, they can be mixed evenly at a speed of 100 to 200 rpm, 100 to 150 rpm, or 150 to 200 rpm.
[0043] Another aspect of the present invention provides use of the thick anti-cracking middle layer coating in construction engineering.
[0044] The thick anti-cracking middle layer coating provided by the present invention has the following beneficial effects:
[0045] 1. Ordinary middle layer or putty is very easy to crack when applied in a single coat over 2mm. For walls with uneven base surfaces, multiple constructions are required. However, after adding coconut fiber, a single coat of 20mm-40mm will not crack. Only a single coat is needed to complete the middle layer construction on walls with uneven base surfaces, saving a lot of labor.
[0046] 2. When coconut fiber is added to replace cement, the overall compressive strength of the material increases rapidly and linearly by 0%-35%. When the compressive strength of the middle layer material reaches 2%, the rising rate area reaches the inflection point and becomes stable. Therefore, its characteristics can be used to replace part of the cement in the middle layer material, thus generating energy-saving and emission reduction benefits.
[0047] 3. Coconut fiber is extracted from waste coconut shells and has a high cost-effectiveness. As a natural renewable material, it has excellent aging resistance in high salinity and alkali environments. While improving the performance of the middle layer material, it also maintains good corrosion resistance and aging resistance. Its excellent toughness can increase the flexibility and ductility of the coating and has excellent crack resistance.
[0048] 4. The present invention makes it easier to spread the coconut fiber with high toughness in the middle layer coating by adding oxidized polyethylene.
[0049] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.
[0050] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.
[0051] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0052] In the following examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0053] Unless otherwise specified, the coconut fiber used in the following is purchased from Qingdao Ouboya Trading Co., Ltd. Indian coconut fiber. Cement is purchased from Shanghai Cement Factory Xiang Brand 42.5 Portland Cement. Silica fume is purchased from Shandong Boken Silicon Material Co., Ltd. Aiken Microsilica Powder 920. Oxidized polyethylene is purchased from Pande (Shanghai) International Trade Co., Ltd. Model PEG-1500. Lightweight aggregate manufacturer Hebei Xinyang 70-100 mesh vitrified microspheres. Desulfurized gypsum is purchased from Lingshou County Yuantong Mineral Products Processing Plant Power Plant Desulfurized Gypsum. Retarder is purchased from Hebei Collaborative Chemical Co., Ltd. HN-302. Cellulose is HK100000S from Hercules. The manufacturer model of chlorinated polyethylene is Dow CPE 702P.
[0054] Example 1
[0055] The present embodiment relates to a thick anti-cracking middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 1.
[0056] Table 1 Weight percentage (wt%) of each component of thick anti-cracking middle layer coating of Example 1:
[0057] Coconut fiber length 9mm 3% Cellulose HK100000S 0.35% 42.5 Portland cement 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 0.6% Light aggregate (vitrified microspheres 70-100 mesh) 21% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0058] Example 2
[0059] The present embodiment relates to a thick anti-cracking middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 2.
[0060] Table 2 Weight percentage (wt%) of each component of thick anti-cracking middle layer coating of Example 2:
[0061]
[0062]
[0063] Example 3
[0064] The present embodiment relates to a thick anti-cracking middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 3.
[0065] Table 3 Weight percentage (wt%) of each component of thick anti-cracking middle layer coating of Example 3:
[0066] Coconut fiber length 9mm 4% Cellulose HK100000S 0.35% 42.5 Portland cement 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 0.6% Light aggregate (vitrified microspheres 70-100 mesh) 20% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0067] Example 4
[0068] The present embodiment relates to a thick anti-cracking middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 4.
[0069] Table 4 Weight percentage (wt%) of each component of thick anti-cracking middle layer coating of Example 4:
[0070] Coconut fiber length 6mm 2% Cellulose HK100000S 0.35% 42.5 Portland cement 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 0.6% Light aggregate (vitrified microspheres 70-100 mesh) 22% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0071] Example 5
[0072] The present embodiment relates to a thick anti-cracking middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 5.
[0073] Table 5 Weight percentage (wt%) of each component of thick anti-cracking middle layer coating of Example 5:
[0074] Coconut fiber length 9mm 2% Cellulose HK100000S 0.35% 42.5 Portland cement 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 1% Light aggregate (vitrified microspheres 70-100 mesh) 21.6% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0075] Example 6
[0076] The present embodiment relates to a thick anti-cracking middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 6.
[0077] Table 6 Weight percentage (wt%) of each component of thick anti-cracking middle layer coating of Example 6:
[0078]
[0079]
[0080] Comparative Example 1
[0081] This comparative example relates to a middle layer coating and a preparation method thereof, which comprises uniformly mixing the wood fiber, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 7.
[0082] Table 7 Weight percentage (wt%) of each component of the middle layer coating of Comparative Example 1:
[0083] Wood fiber 1mm 2% Cellulose HK100000S 0.35% Cement 42.5 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 0.6% Light aggregate (vitrified microspheres 70-100 mesh) 22% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0084] Comparative Example 2
[0085] This comparative example relates to a middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber with a length of 12 mm, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 8.
[0086] Table 8 Weight percentage (wt%) of each component of the middle layer coating of Comparative Example 2:
[0087]
[0088]
[0089] Comparative Example 3
[0090] This comparative example relates to a middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber length, the cellulose, the cement, the silica fume, the oxidized polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 9.
[0091] Table 9 Weight percentage (wt%) of each component of the middle layer coating of Comparative Example 3:
[0092] Coconut fiber length 9mm 2% Cellulose HK100000S 0.35% Cement 42.5 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 0.6% Light aggregate (white vermiculite 70-100 mesh) 22% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0093] Comparative Example 4
[0094] This comparative example relates to a middle layer coating and a preparation method thereof, which comprises uniformly mixing the coconut fiber length, the cellulose, the cement, the silica fume, the chlorinated polyethylene, the light aggregate, the desulfurized gypsum and the retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 10.
[0095] Table 10 Weight percentage (wt%) of each component of the middle layer coating of Comparative Example 4:
[0096]
[0097]
[0098] Comparative Example 5
[0099] This comparative example relates to a middle layer coating and a preparation method thereof, which comprises uniformly mixing the cellulose, cement, silica fume, oxidized polyethylene, light aggregate, desulfurized gypsum and retarder at a speed of 100 to 200 rpm. Specifically, the weight percentage of each component is shown in Table 11.
[0100] Table 11 Weight percentage (wt%) of each component of the middle layer coating of Comparative Example 5:
[0101] Cellulose HK100000S 0.35% 42.5 Portland cement 45% Silica fume 200 mesh 10% Oxidized polyethylene (polyethylene glycol) 1% Light aggregate (vitrified microspheres 70-100 mesh) 23.6% Desulfurization gypsum 20% Retarder (HN-302) 0.05% total 100%
[0102] Test Method
[0103] 1. Test method for initial drying crack resistance: JG / T 24-2000
[0104] 2. Corrosion resistance test method: GB / T 10125-1997
[0105] 3. Test method for aging resistance: GB / T 1865
[0106] 4. Flexibility test method: JC / T 1004-2006 according to Appendix B
[0107] 5. Compressive strength method: JG / T 283-2010 6.12
[0108] 6. Thermal conductivity: GB / T 10294-2008
[0109] The test results of each embodiment and comparative example are shown in Table 12.
[0110] Table 12
[0111]
[0112] As can be seen from Table 12, adding coconut fiber can greatly increase the thickness of a single coat and keep it from cracking in the early stage, but when using coconut fiber of other lengths, the thickness of a single coat is reduced, and the initial cracking resistance is also reduced. The single coat and initial cracking of the experiment without adding coconut fiber are much lower than those of the material with added coconut fiber. The compressive strength of coconut fiber increases significantly, and its compressive strength is reduced when chlorinated polyethylene is used. Adding coconut fiber has significantly improved corrosion resistance and artificial aging resistance, while other plant fibers are not effective in corrosion resistance and aging. Adding coconut fiber has significantly improved flexibility, but using coconut fibers of different lengths has a reduced effect on flexibility, and using chlorinated polyethylene has a significant reduced effect on flexibility. Adding coconut fiber improves thermal insulation, but using coconut fibers of different lengths has a reduced effect on thermal insulation.
[0113] In the above formula, cement is 45%, and the relationship between coconut fiber and compressive strength is as follows:
[0114] Table 13
[0115] 9MM coconut fiber Compressive strength MPa 0% 2.8 1% 2.9 2% 3.4 3% 3.5 4% 3.7 5% 3.7 6% 3.8
[0116] As can be seen from the table above, the rate of increase is fastest when the amount of coconut fiber added is between 0% and 2%. As the amount of coconut fiber added increases further, the rate of increase in compressive strength slows down, and when it exceeds 4%, the increase in compressive strength is not obvious. Therefore, considering the cost, the weight percentage of coconut fiber is 1-4%.
[0117] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.
[0118] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A thick anti-cracking middle layer coating, wherein the raw materials of the coating include the following components by weight percentage: Coconut fiber 4%; Cement 45%; Silica fume 10%; Oxidized polyethylene 0.6%; Light aggregate 20%; Desulfurized gypsum 20%; Retarder 0.05%; Cellulose 0.35%; The length of the coconut fiber is 9mm; The cellulose is cellulose HK100000S; The cement is 42.5 Portland cement; The silica fume is 200 mesh; The oxidized polyethylene is PEG-1500; The light aggregate is vitrified microspheres 70-100 mesh; The retarder is HN-302.
2. The method for preparing the thick anti-cracking middle layer coating as claimed in claim 1 comprises mixing coconut fiber, cement, silica fume, oxidized polyethylene, light aggregate, desulfurized gypsum, retarder and cellulose.
3. Use of the thick anti-cracking middle layer coating as claimed in claim 1 in the field of construction.
Citation Information
Patent Citations
High-performance thermal insulation building material
CN108840615A
Sprayable thermal insulation mortar with high water resistance
CN109053113A